Diagnosis of Drug-Resistant Tuberculosis: Rapid Evaluation of Drug Susceptibility with Nanopore Targeted Sequencing. - Chen, Jun; Fan, Qijing; Gong, Shiwei; Guo, Jianjian; Rao, Youyi; Chen, Lifeng; Wang, Ying; Liao, Rui; Zhang, Zhengbin; Liu, Chang; Wu, Ming; Chen, Shi; et al. (Clinical Chemistry, 2025)
Background Whole-genome sequencing (WGS) has limitations in clinical diagnostics due to host DNA interference and lower pathogen load in clinical samples compared to cultured isolates, which reduce the effective sequencing depth and compromise the detection of resistance-associated mutations. As our understanding of the relationship between genotypes and phenotypes improves, targeted next-generation sequencing (tNGS) is emerging as a promising tool for predicting drug resistance in Mycobacterium tuberculosis. This study aimed to evaluate the performance of nanopore targeted sequencing (NTS) in detecting drug resistance in Mycobacterium tuberculosis. Methods We employed NTS to assess the drug susceptibility of 105 M. tuberculosis isolates and 175 clinical samples to 15 antituberculosis (TB) drugs, using phenotypic drug susceptibility testing as the gold standard. Results For cultured isolates, the overall sensitivity of NTS for 15 anti-TB drugs was 90.2% (95% CI, 86.5–93.2%), specificity 95.6% (94.2–96.8%), positive predictive value (PPV) 86.8% (83.1–89.8%), negative predictive value (NPV) 96.9% (95.7–97.7%), and overall agreement 94.3% (93.0–95.5%). The Cohen Kappa was 0.847 (0.814–0.880). For direct clinical samples, the sensitivity was 93.2% (89.5–95.9%), specificity 98.6% (98.0–99.1%), PPV 89.9% (86.0–92.8%), NPV 99.1% (98.6–99.4%), and agreement 98.0% (97.3–98.5%), with a Cohen Kappa value of 0.904 (0.876–0.931). NTS demonstrated a limit of detection of 500 copies/mL and could detect 4% heteroresistance. Conclusions NTS is a rapid and efficient diagnostic tool that reliably predicts drug resistance and shows potential to support resistance profiling in the clinical setting.